2020
DOI: 10.1177/1753193420926097
|View full text |Cite
|
Sign up to set email alerts
|

The strengths of one-, two-, and three-weave Pulvertaft tendon repairs

Abstract: We tested the tensile strength of the proximal juncture of tendon grafts with Pulvertaft tendon repairs in 18 cadaveric digital flexor tendons. These tendons were divided into three groups of six: single, two, or three weaves. Each of the interlacing weaves was secured with eight anchoring sutures. The specimens were loaded in a biomechanical tester until failure. The ultimate tensile strength did not show any significant differences across all three groups with statistical power of 0.77. The mean tendon elong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Dear Editor, We thank Mr Hems for his comments on our articles. In our first article (Choke et al, 2020), we emphasized that our main focus was on the effect of weaves and thus we had to control all other factors, namely suture material and repair configuration. We found that two-weave Pulvertaft is sufficient to provide adequate repair strength (91 N) and ease the complexity of surgery due to the additional weave and increased number of sutures that add to the bulk of the repair.…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, We thank Mr Hems for his comments on our articles. In our first article (Choke et al, 2020), we emphasized that our main focus was on the effect of weaves and thus we had to control all other factors, namely suture material and repair configuration. We found that two-weave Pulvertaft is sufficient to provide adequate repair strength (91 N) and ease the complexity of surgery due to the additional weave and increased number of sutures that add to the bulk of the repair.…”
Section: Replymentioning
confidence: 99%
“…The first study by Choke et al (2020) investigates the effect of the number of weaves on the initial tensile strength of the repair by comparing one, two and three weaves. The results suggest that the twoweave repair had similar tensile strength (91 N) to the three-weave repair (89 N).…”
mentioning
confidence: 99%
“…It is commonly used during upper extremity reconstruction when end-to-end tendon repairs and nerve transfers are not possible. 2-4 As the PT conveys significant strength, it will likely continue in clinical practice. 5-7…”
Section: Introductionmentioning
confidence: 99%
“…The strengths of four different suture types in Pulvertaft tendon reconstruction Dear Editor, In our previous article 'A biomechanical study of strengths of one-, two-, or three-weave Pulvertaft tendon repair' (Choke et al, 2020), we ascertained that the two-weave Pulvertaft repair is a satisfactory choice for tendon reconstruction. Following on from that study, we wanted to evaluate if suture type had any effect on the Pulvertaft tendon construct.…”
mentioning
confidence: 99%
“…Each flexor tendon was divided into two separate lengths, where one end was made a donor tendon and another end was made a recipient tendon, in order to control for tendon dimensions. The Pulvertaft weave was constructed, two-weaves secured with eight sutures (simple sutures), with the same technique as previously described (Choke et al, 2020). The same biomechanical testing protocol was used to measure the ultimate tensile strength and tendon elongation at maximum load.…”
mentioning
confidence: 99%